Analyzing Delivery Area/Zone Tagging Techniques Within Fulfillment Centres For Last Mile Delivery Orders - Younus, Muhammad; Nurmandi, Achmad; Suswanta, Suswanta; Rehman, Abdul (Riviera Publishing, 2023)
Last-mile delivery in e-commerce logistics is crucial and difficult, affecting consumer happiness and operational efficiency. Fulfillment centers use delivery area/zone marking to ease this operation. This study examines fulfillment center methods for optimizing last-mile delivery orders. This research first examines delivery area/zone labeling methods. These methods break geographical regions into smaller manageable parts for resource allocation and route optimization. Grid-based zoning, distance-based tagging, and contemporary machine learning methods for dynamic and adaptive zone identification will be investigated. The study then examines delivery area tagging implementation factors. Zone tagging success depends on population density, order frequency, traffic patterns, and delivery time windows. Emission regulations and sustainability targets will also be examined. Delivery area/zone tagging technology and tools are also examined. GPS tracking, GIS mapping, and real-time data analytics enable effective monitoring and modifications. IoT devices and predictive analytics will also be assessed for their impact on delivery performance. This study concludes with the benefits and drawbacks of delivery area/zone labeling. Delivery time, operational expenses, and customer experience improve. Fulfillment focuses face data privacy, algorithmic biases, and system scalability issues. In conclusion, this study examines fulfillment center delivery area/zone labeling for last-mile delivery orders. E-commerce and logistics stakeholders may maximize last-mile delivery by knowing the different methods, technology, and factors affecting them.